Study of the Patency of Small Arterial Branches after Stent Placement with an Experimental in Vivo Model - Masuo, Osamu; Terada, Tomoaki; Walker, Gary; Tsuura, Mitsuharu; Matsumoto, Hiroyuki; Tohya, Kazuo; Kimura, Michio; Nakai, Kunio; Itakura, Toru (American Journal of Neuroradiology, 2002)
BACKGROUND AND PURPOSE: The patency of intracranial perforating arteries after stent placement is unknown despite the general clinical use of intracranial arterial stenting.METHODS: We deployed stainless steel stents in the abdominal aorta across the lumbar artery in eight normal rabbits in which the diameters of the abdominal arterial vessels were similar to those of human intracranial arteries. We evaluated the patency via angiographic and scanning electron microscopic methods 3 months after stent placement. Histopathologic evaluation was also performed for one rabbit.RESULTS: The lumbar arteries were patent, even when stent struts crossed the ostium, except in one rabbit in which intimal dissection occurred intraoperatively. The scanning electron microscopy showed that the regenerative endothelium had grown onto the strut at the ostium of the lumbar artery.CONCLUSION: We confirmed the patency of the lumbar arteries in this study by using normal rabbits. Thus, intracranial stenting may not pose a risk of occluding perforating arteries of the same diameter of the lumbar artery, even if stent struts cover the ostium.